Evaluating Social Impact : A Case Study of Baitut Tamkin Lombok using SROI Analysis - Mia Sari; Nadia Nurul Izza; Siti Salmah; Abdul Haris (Islamic Marketing Review, 2023)
This paper aims to evaluate the social impact of the BTTM Tazkia project in Lombok using Social Return on Investment (SROI) analysis as the main method. A qualitative approach was used to explore the impacts associated with these projects, while in-depth interviews were used as the main instrument for data collection. The results of the SROI analysis produce a ratio of 1:3.98, reflecting that each investment unit of IDR 1 produces a social impact and value of IDR 3.98. These findings illustrate the significant positive impact of this program in creating social value that covers various aspects, including financial, social and spiritual aspects. These findings indicate that the SROI approach and qualitative approach used provide a deep understanding of the impact of BTTM Tazkia's holistic development projects in Lombok. These results have strong implications for designing, managing, and measuring the impact of similar programs in the future, as well as fostering a broader understanding of the social value created by organizations in sustainable development efforts.